Peran Zakat Terhadap Pemberdayaan Dan Kesejahteraan Mustahiq - Akmalur Rijal (Universitas Islam Lamongan, 2019)
Poverty is a crucial problem that is being faced by all nations in the world, including Indonesia. This condition will certainly disrupt national development and stability. Therefore, what is needed now is a solution that can help overcome the problems. The poverty is defined as the inability of a person to fulfill his basic needs because of his powerlessness in accessing or mastering economic resources. The inequality of economic development is one of the causes of poverty. Welfare is a condition that is a hope for every citizen. But in reality not all citizens can easily get welfare. The empowerment of productive zakat funds has a very large role in the business mustahiq, because of the limitation to increase capital in its business, so that zakat funds become one of the solutions to advance business mustahiq. Productive zakat has the specificity of being channeled to the production business of mustahiq. Productive businesses carried out by mustahiq with capital from productive zakat. His efforts are expected to be able to continue to grow, so that being able to raise the economic level of mustahiq so that achieving prosperity can even become muzakki. Keywords: Zakat, Mustahiq, Zakat Empowerment